Effectiveness of Student Online Learning in Indonesia - Hafizh, Muhammad; Asril, Zainal (Ahlussunnah: Journal of Islamic Education, 2023)
The breakdown of parents' concentration and various new problems in the Lima Rakyat community regarding the teaching and learning process during Covid 19 which was regulated by several schools and madrasas in the Lima Kunci sub-district have raised parents' concerns about their children's education. This research aims to overcome learning problems during the Covid 19 pandemic, especially in the five Batusangkar communities so that ideal education can be achieved by balancing government regulations regarding the pandemic with effective and efficient learning process standards for students. This type of research is descriptive qualitative, describing the learning process during the pandemic, identifying all learning problems in the field by interviewing students and relevant to school policies to maintain the quality of the teaching and learning process. Research findings on the effectiveness of online learning have given rise to a new polemic in five Batusangkar communities where the limited facilities and infrastructure in the technology sector and the weak economy of the community to buy internet quotas and android cellphones as well as a limited signal in rural areas, apart from economic constraints and study concentration, new problems have emerged, namely controlling online learning is difficult for parents to do because parents' lack of technology results in children wandering around playing online games and doing and using android only as a game application that is not useful so that online learning is not carried out well because android is often used for things that are not useful. useful and the occurrence of online gambling, opening adult sites, and creating negative WhatsApp groups. Ideally, school policy is recommended in providing assignments in online learning and increasing parental control in online learning in order to create effective and efficient learning. The research results can be used as initial data for subsequent researchers to study this problem in the context of different issues and findings.